Eco-Theology of Water from the Perspective of Hadith: Thematic Study of Al-Mā' Term - Achmad Dahlan; Asrul Asrul (Jurnal Ushuluddin, 2022)
Water is a vital natural resource for human life. The study of water has attracted the attention of scholars and scientists along with the ongoing destruction of nature. The combination of the two viewpoints of scientists and clergy on environmental issues led to a new study called eco-theology. This fact encourages researchers to conduct research on water eco-theology from a hadith perspective. The purpose of this study is to formulate the concept of the relationship between religious texts (hadith) and the environment which has become the biggest problem of mankind today. This study uses a qualitative method with a library research approach, namely reading and exploring references related to the theme of the study. The results of the study show that the study of the term al-mā' in the texts of the prophet's hadith includes three main aspects, namely joint ownership of water (social function), oriented towards survival (ecological function), and water conservation (conservation function). The findings in this study are (1) attached to the social dimension of water, both regarding the basic needs of humans, and animals, including for agriculture to disaster emergencies. (2) water has an important role in the formation of ecology that encourages the emergence of human awareness to treat water well for the realization of an ideal living environment. (3) saving water from the threat of damage is also an important part of the Prophet's hadith about al-mā'. These three aspects confirm the relationship between religious texts and science.